Carcass traits and value of meat and byproducts of buffalo - MUTHUKUMAR, M; KANDEEPAN, G; PATHAK, VIKAS; RATHOD, K S; AMBADKAR, R K; KULKARNI, V V (The Indian Journal of Animal Sciences, 2018)
A study was conducted to collect data on carcass traits covering 1,005 buffaloes across India. The results indicated that the live weight and dressed carcass weight of buffaloes ranged from 174.82 to 422.83 kg and 79.08 to 213.73 kg, respectively with an average dressing percentage of 47.92%. There was a significant difference in the overall dressing percentage and overall yield of blood, skin and intestine of buffaloes of different body weight groups, viz. less than 200 kg (group 1), between > 200 to <300 kg (group 2), >300 to <400 kg (group 3) and more than 400 kg (group 4). It was also found that the majority of the buffalo slaughtered were in the weight group of >300 to >400 kg (43.08%) and >200 to <300 kg (40%). The overall average live weight of buffaloes from southern part of the country (Andhra Pradesh) was lower (278.26 kg) when compared to the northern part (Uttar Pradesh). Further, the proportion of low body weight buffaloes (below 300 kg) utilized for meat production was more in Andhra Pradesh (70%) and in Uttar Pradesh proportionately higher body weight animals (more than 300 kg) were slaughtered more (Mathura 92.33%, Bareilly 46.8%). The yield of edible (head, feet, stomach with content, heart, liver, kidney and fat) and inedible byproducts (blood, skin, intestine with content and lungs) as percentage of live buffalo weight were 27.61 and 24.45%, respectively. In terms of commercial value of buffalo carcass, major revenue comes from meat (88.66%), followed by skin (6.6%) and edible offal (5.0%).